Analisis Faktor-Faktor Yang Mempengaruhi Kurangnya Minat Mahasiswa Sidoarjo Menjadi Nasabah Bank Syariah - Eka Vebryl Maretha; Fitri Nur Latifah; Masruchin Masruchin (ITB AAS INDONESIA Surakarta, 2022)
This research is motivated by the large number of people in Indonesia, especially students in the city of Sidoarjo, who still lack Islamic knowledge about Islamic banking, its profit system and its services. This study aims to determine the factors that influence the lack of interest in Sidoarjo students to become customers of Islamic banks. The population of this research is students in the city of Sidoarjo, with a sample of 99 respondents. The approach in this study is a quantitative approach using primary data. The method used is multiple linear regression analysis technique. Based on the results of the study, understanding of sharia has no effect on the interest of students in Sidoarjo to become customers of Islamic banks, while profit sharing and services have a positive influence on students' interest in becoming customers of Islamic banks.